Uvajanje plavanja po Fredovi metodi v predšolskem obdobju in prvem razredu osnovne šole - Jazbec, Jure (Šport (Ljubljana), 2016)
Games in water and swimming are included in both the kindergarten curriculum and the curriculum for the first grade of primary school. We can achieve some global objectives through swimming. In order to achieve as many objectives as possible, the correct teaching method has to be selected. We believe that Fred's swim teaching method is very suitable for this age group because it provides safety for the children and enables fast progress.
Keywords: classical swim teaching method; Fredova metoda učenja plavanja; Fred's swim teaching method; klasična metoda učenja; plavanje; predšolska vzgoja; preschool education; sport; swimming; šport; učenje plavanja